# DIFFERENTIATION FORMULAS BASIC ALGEBRAIC DIFFERENTIATION d n du ▪ u = nu n −1 dx dx d (Cu ) = C du ▪ dx dx d du dv u±v= ± ▪ dx dx dx d dv du uv = u +v ▪ dx dx dx du dv v −u d u dx dx ▪  = dx  v  v2 d  C  −C dv ▪ ⋅  = dx  v  v2 dx d  v  1 dv

▪  = ⋅ dx  C  C dx du d ▪ u = dx dx 2 u 1  1 d  n  1 n −1 du ▪ u  = ⋅u ⋅ dx   n dx    LOGARITHMIC DIFFERENTIATION d (log a u ) = 1 log a e du ▪ dx u dx 1 du d ▪ (ln u ) = ⋅ dx u dx EXPONENTIAL DIFFERENTIATION

d u du C = C u ⋅ lnC ⋅ dx dx

( )

TRIGONOMETRIC DIFFERENTIATION d ▪ (sin u ) = cos u ⋅ du dx dx d (cos u ) = − sin u ⋅ du ▪ dx dx d du 2 (tan u ) = sec u ⋅ ▪ dx dx d 2 (cot u ) = − csc u ⋅ du ▪ dx dx d (sec u ) = sec u tan u ⋅ du ▪ dx dx d (csc u ) = − csc u cot ⋅ du ▪ dx dx INVERSE TRIGONOMETRIC DIFFERENTIATION d du 1 ▪ ⋅ sin −1 u = 2 dx dx 1− u d −1 du ▪ cos−1 u = ⋅ 2 dx dx 1− u

d −1 du csc −1 u = ⋅ 2 dx u u − 1 dx HYPERBOLIC DIFFERENTIATION d ▪ (sinh u ) = cosh u ⋅ du dx dx d du ▪ (cosh u ) = sinh u ⋅ dx dx d 2 ▪ (tanh u ) = sec h u ⋅ du dx dx d du 2 ▪ (coth u ) = − csch u ⋅ dx dx d ▪ (sec hu ) = − sec hu tanh u ⋅ du dx dx d du (csc hu ) = − csc hu coth u ⋅ ▪ dx dx
▪ INVERSE HYPERBOLIC DIFFERENTIATION d 1 du ▪ sinh−1 u = ⋅ 2 dx u + 1 dx

(

)

d −1 du csc h −1u = ⋅ 2 dx dx u 1+ u INTEGRATION FORMULAS BASIC INTEGRATION
▪ ▪

(

)

∫ dx = x + C

▪ ∫ af (x )dx = a ∫ f ( x )dx ; a = constant 1 ▪ f (x )dx = af (x )dx a ▪ [ f (x ) ± g (x )]dx = f (x )dx ± g (x )d x

∫ ∫

GENERAL POWER FORMULA

( )

(

)

(

)

INTEGRANDS YIELDING TO NATURAL LOGARITHMS du ▪ = ln u + C u EXPONENTIAL INTEGRATION

∫ x dx = n + 1 + C ; n ≠ -1,n = constant
n

x n +1

(

)

d u du e = eu dx dx

( )

d 1 du tan −1 u = ⋅ dx 1 + u 2 dx d − 1 du ▪ cot −1 u = ⋅ dx 1 + u 2 dx d 1 du ▪ sec−1 u = ⋅ 2 dx u u − 1 dx

( ( (

) )

)

d 1 du cosh−1 u = ⋅ 2 dx u − 1 dx d 1 du ▪ tanh−1 u = ⋅ ;1 > u2 dx 1 − u 2 dx d −1 du ▪ coth−1 u = 2 ⋅ ; u 2 > 1 dx u − 1 dx d −1 du −1 ▪ sec h u = ⋅ 2 dx dx u 1− u

(

)

( ( (

) ) )

au +C ▪ eu du = eu + C ▪ au du = ln a where: e = 0.718 = constant a = constant other than e DEFINITE INTEGRALS

∫a f (x)dx = f (x)]a = f (b) − f (a)
b

b

∫a f (x )dx = −∫b f (x)dx

b

a

∫ f (x)dx = ∫ f (x)dx + ∫ f (x)dx
a a c

b

c

b

∫ f (x )dx = ∫ f (y )dy
a a

b

b

where: a = lower limit b = upper limit

BASIC TRIGONOMETRIC INTEGRATION ▪ ▪ ▪ ▪ ▪

∫ ∫ cos udu = sin u + C 2 ∫ sec udu = tan u + C 2 ∫ csc udu = − cot u + C
sin udu = − cos u + C

IF BOTH ARE ODD, TRANSFORM LOWER POWER CASE 3: n = EVEN
n2

CASE 2:

∫ sec =udu or ∫ csc udu n EVEN
n n

∫u

du u −a
2 2

=

1 u sec −1 + C a a

sin n u = (sin 2 u )
transform

sec u = sec
n

n

n−2

u (sec u ) u (csc u )
2 2

2

BASIC HYPERBOLIC INTEGRATION ▪ ▪ ▪ ▪ ▪ ▪

transform

csc u = csc
n2
2

n−2

cos u = (cos u)

n

2

transform

1 Use sin2 u = (1 − cos2u ) or CASE 3: tan m u sec n udu or 2 csc u cot udu = − csc u + C ▪ 1 cos2 u = (1 + cos 2u ) cot m u csc n udu ▪ tan udu = − ln cos u + C 2 n IS EVEN; CASE 4: sin mu cos n udu SIMILAR TO CASE 2 ▪ tan udu = ln sec u + C m & n ARE EVEN, TRANSFORM BOTH CASE 4: tan m u sec n udu or SAME AS CASE 3 ▪ cot udu = ln sin u + C CASE 5: cot m u cscn udu ▪ sec udu = ln sec u + tan u + C ▪ sinα cosβ = 1 [sin( + β ) + sin( − β )] α α m = ODD 2 tanm u secn udu = ▪ csc udu = ln csc u − cot u + C ▪ cosα cosβ = 1 [cos( + β) + cos( − β)] α α 2 tanm−1 u secn−1 u(tanu secudu) TRANSFORMATIONS OF TRIGONOMETRIC 1 transform α α ▪ sinα sinβ = − [cos( + β) − cos( − β)] FUNCTIONS 2 cotm u cscn udu = SINE/COSINE CASE 1: n = ODD TANGENT/COTANGENT/SECANT/COSECANT cotm−1 u cscn −1 u(cot u cscudu) n n −1 CASE 1: tan n udu or cotn udu transform sin u = sin u (sin u )

sec u tan udu = sec u + C

transform

where: sec u = 1 + tan u csc2 u = 1 + cot2 u

∫ sinh udu = cosh u + C ∫ cosh udu = sinh u + C 2 ∫ sec h udu = tanh u + C

∫ ∫ ∫ ∫ ∫ ∫

∫ ∫

∫ csch udu = −cothu + C
2

∫ sec hu tanh udu = − sec hu + C
∫ csc hu coth udu = − csc hu + C

INTEGRALS YIELDING TO INVERSE HYPERBOLIC FUNCTIONS du u ▪ = sinh −1 + C 2 2 a u +a du −1 u = cosh +C ▪ a u 2 − a2

∫ ∫

▪ ▪

∫ a2 − u 2 = tanh a + C ,|u|<a du 1 u ∫ u − a = − a coth a + C , u >a
−1 2 2
2

du

−1 u

2

cos u

cos u = cos

n

n −1

u (cos u )

tan u = tan

n

n−2

u (tan 2 u )
transform

Use sin 2 u + cos 2 u = 1 CASE 2: sin m u cos n udu ONE EXPONENT IS ODD; SIMILAR TO CASE 1

sin u

cot n u = cot n − 2 u (cot 2 u )

where: tan u = sec u −1 cot2 u = csc2 u − 1

2

2

transform

INTEGRALS LEADING TO INVERSE TRIGONOMETRIC ▪ FUNCTIONS du u ▪ ▪ = sin−1 + C a a2 − u 2 du 1 u ▪ = tan−1 + C a a2 + u 2 a

∫u

du a −u
2 2

=

−1 u sec h −1 + C a a

∫u

du a +u
2 2

=

−1 u csc h−1 + C a a

Mxz = ∫ yc dV a V ▪ z=0 xc dV ▪ S= ∫a ∫x dxdy b y ∫a ∫y dydx 2 1 VOLUME DISK METHOD 2 note: the centroid always lies on the axis of rotation LENGTH OF AN ARC – S 2 dz 1+ z V =π ∫a r h ... y . My = APPLICATIONS AREA UNDER A CURVE A = LW . y ) ▪ x = My . x = x on the right xl = x on the left 1 ▪ z = tan x 2 ▪ du = ∫a V b Mxz ▪ y= . Mx = ∫ yc dA a A xc dA ▪ x = Myz . log a 1 = 0 log a a = 1 log a ( xy ) = log a x + log a y x log a   = log a x − log a y  y log a y x = x log a y 1 log a y x log a a x = x log a x e x − e− x e x + e− x e x + e− x coth x = x − x e −e 2 sec hx = x − x e +e 2 csc hx = x − x e −e BASIC HYPERBOLIC FORMULAS tanh x = cosh 2 x − sinh 2 x = 1 cosh x + sinh x = e x cosh x − sinh x = e− x sinh 2 x = 2sinh x cosh x cosh 2 x = cosh 2 x + sinh 2 x coth 2 x = csc h2 x + 1 tanh 2 x + sec h2 x = 1 sinh( x + y ) = sinh x cosh y + cosh x sinh y cosh( x + y ) = cosh x cosh y + sinh x sinh y TRIGONOMETRIC IDENTITIES ▪ RECIPROCAL IDENTITIES 1 sin θ 1 sec θ = cos θ 1 cot θ = tan θ csc θ = tan( x − y ) = tan x − tan y 1 + tan x tan y y= TANGENT AND COTANGENT sin θ tan θ = cos θ cos θ cot θ = sin θ PYTHAGOREAN IDENTITIES sin 2 θ + cos 2 θ = 1 1 + tan 2 θ = sec 2 θ 1 + cot 2 θ = csc 2 θ COFUNCTION IDENTITIES sin(90 − θ ) = cos θ csc ( 90 − θ ) = sec θ sec ( 90 − θ ) = csc θ cos ( 90 − θ ) = sin θ cot ( 90 − θ ) = tan θ SUM & DIFFERENCE FORMULAS sin( x + y ) = sin x cos y + cos x sin y sin( x − y ) = sin x cos y − cos x sin y cos( x + y ) = cos x cos y − sin x sin y cos( x − y ) = cos x sin y + sin x sin y tan x + tan y tan( x + y ) = 1 − tan x tan y a =x EXPONENTIAL FUNCTIONS log a x a0 = 1 a x+ y = a x ⋅ a y ax ay (a x )r = a rx a x− y = a log a x = x a x = e x ln a e ln x DOUBLE ANGLE FORMULAS sin 2θ = 2 sin θ cos θ cos 2θ = cos 2 θ − sin 2 θ cos 2θ = 1 − 2 sin 2 θ 2 tan θ tan 2θ = 1 − tan 2 θ POWER REDUCING FORMULAS 1 − cos 2θ sin 2 θ = 2 1 + cos 2θ 2 cos θ = 2 1 − cos 2θ 2 tan θ = 1 + cos 2θ HALF-ANGLE FORMULAS sin θ 2 = = 1 − cos θ 2 cos tan tan cot cot θ 2 INVERSE HYPERBOLIC FUNCTIONS EXPRESSED AS LOGARITHMIC FUNCTIONS sinh −1 x = ln x + x 2 + 1 cosh −1 2 θ 2 =x HYPERBOLIC FUNCTIONS sinh x = e x − e− x 2 e x + e− x cosh x = 2  1  1 + x  sec h −1 x = ln  1 ± 1 − 1   tanh −1 x = ln  x   x  2  1− x   1  1 1  x +1  −1 coth −1 x = ln   csc h x = ln  x ± x 2 + 1    2  x −1    ( x = ln ( x ± ) x −1) θ 2 θ 2 θ 2 1 + cos θ 2 1 − cos θ = sin θ sin θ = 1 + cos θ sin θ = 1 − cos θ 1 + cos θ = sin θ SINE LAW a b c = = sin A sin B sin C .. y = f(x)  dx  2 PROPERTIES OF LOGARITHM If a y = x then log a x = y . if otherwise TECHNIQUES OF INTEGRATION INTEGRATION BY PARTS ▪ sin u = ▪ cos u = 2z 1+ z2 1 − z2 1+ z 2 VOLUME RING METHOD V =π ▪ S= ri = inner radius ∫ udv = uv − ∫ vdu INTEGRATION BY TRIGONOMETRIC SUBSTITUTION CASE 1: a 2 − u 2 ▪ u = a sinθ ▪ du = a cosθdθ CASE 2: a 2 + u 2 ▪ u = a tanθ ▪ du = a sec2 θdθ CASE 3: u 2 − a 2 ▪ u = a secθ ▪ du = a secθ tanθdθ RECIPROCAL SUBSTITUTION ∫a ( ro b b 2 − ri 2 ) h ...WALLI’S FORMULA ∫0 π 2 sinm u cosn u = [(m − 1)(m − 3)(m − 5). y )dx dy ▪ note: the centroid lies on axis of symmetry CENTROID OF VOLUMES C ( x . z ) ∫a ∫y b x2 1 f (x . Myz = b 2 nd assume y = constant 1st b y2 ∫a ∫x b x2 1 1st f (x . yh = upper y yl = lower y r INTEGRATION OF RATIONAL FUNCTIONS OF SIN & COS ∫a (xr − xl )dy .n = 2or1] •α (m + n)(m + n − 2)(m + n − 4). ro = outer radius ∫ b 1+  a  dx   dy .. r = radius. t = thickness ▪ b du 1 a+u ln +C 2a a − u CENTROID OF AREAS C ( x . L = length. h = height 2 b ∫ b 1+  a  dy   dx . y )dy dx 2 nd 1 assume x = constant AREA BETWEEN TWO CURVES AREAS BY DOUBLE INTEGRATION ▪ ▪ 1 ▪ x= z ▪ dx = −dz z 2 ▪ A= ▪ A= ∫ ( yh − yl )dx a b b .m = 2or1][(n − 1)(n − 3)(n − 5).m + n = 2or1 where: α = π . if both m & n are even 2 α = 1 . W = width ∫a ∫a A b Mx ▪ y= . x = g(x)  dy  2 OTHER INTEGRATION FORMULAS ▪ ▪ VOLUME SHELL METHOD +C MULTIPLE INTEGRALS DOUBLE INTEGRALS ∫ u 2 − a 2 = 2a ln u + a ∫ a2 − u 2 = b du 1 u−a V = 2π ∫arht .

COSINE LAW a 2 = b 2 + c 2 − 2bc cos A b 2 = a 2 + c 2 − 2ac cos B c 2 = a 2 + b 2 − 2ab cos C LAW OF TANGENTS 1 tan ( A − B) a −b 2 = a + b tan 1 ( A + B ) 2 PRODUCT TO SUM FORMULAS 1 [cos( x − y ) − cos( x + y )] 2 1 cos x sin y = [ cos( x + y ) + cos( x − y ) ] 2 1 sin x cos y = [sin( x + y) + sin( x − y ) ] 2 1 cos x sin y = [sin( x + y) − sin( x − y ) ] 2 sin 2 x sin x cos x = 2 sin x sin y = MOLLWEICLE’S EQUATION 1 sin ( A − B) a−b 2 = 1 C cos C 2 1 cos ( A − B) a+b 2 = 1 C sin C 2 SUM TO PRODUCT FORMULAS  x+ y  x− y sin x + sin y = 2 sin   cos    2   2  x+ y  x− y  sin x − sin y = 2 cos   sin    2   2   x+ y  x− y cos x + cos y = 2 cos   cos    2   2   x+ y  x− y cos x − cos y = −2sin   sin    2   2  .